PELAKSANAAN PERJANJIAN KERJA DI PABRIK SAWIT PT. ANUGERAH TANI MAKMUR (ATM) MAREDAN - Suratun Suratun; Evi Deliana; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A probationary work agreement is an agreement made between a worker and a company. This is in accordance with Article 1320 of the Civil Code (hereinafter KUHPerdata) which states that the terms of the agreement must be an agreement from the party making the agreement, the ability to make an agreement, there are certain objects or things, lawful causes. The provisions of Article 52 of Law Number 13 Year 2003 concerning Manpower are a development of Article 1320 of the Civil Code, which states that the four conditions above are required for the validity of an agreement. The provisions for workers in the probationary period agreement are in Article 60 of Law Number 13 of 2003 concerning Manpower, so the probation period is not more than 3 months. Meanwhile, workers who are contract employees are not allowed to stipulate an agreement for a probation period.This type of research is sociological legal research, namely research that examines the legal aspects by looking at the applicable laws and comparing with the implementation obtained in the field, this research was conducted at PT. Anugerah Tani Makmur Maredan, Tualang District, Siak Regency. From the results of this study, there are three things that can be concluded. First, the implementation of a work agreement on probation, the second is the reason for not implementing the agreement in accordance with the Manpower Act, the third is the efforts that the parties can make.Thus the probationary work agreement that exceeds and does not comply with the provisions of Article 1320 of the Civil Code, Article 52 and Article 60 of Law Number 13 of 2003 concerning Manpower which makes the contract made null and void by law. The author's suggestion, first it is hoped that the parties in the making or stipulation and implementation of the work agreement for the probationary period of Article 1 must be corrected in the future. Second, in signing a work agreement, you must read carefully the contents of the agreement and seek deliberation with the parties to improve the contents of the agreement so that it can benefit both parties and more clearly know whether the worker / laborer is a contract / permanent employee, can be understood from the type of work agreement received.Key words: implementation-work agreement-probationary period